Purificação e estudos bioquímicos de exo-poligalacturonase (pectinase) produzida pelo fungo termofílico Rhizomucor pusillus, em cultivo submerso e aplicação na extração de sucos de frutas e hidrólise enzimática do bagaço de cana-de-açúcar - Trindade, Lucas Vinícius [UNESP] (2015)
Pectinases are a group of enzymes capable of degrading pectic polysaccharides (pec-tin). These enzymes are used in the industry for production of fruit juices, wines, tex-tiles, paper, tea, oils, etc. This study aimed to produce, purify and characterize an exo-poligacturonase (exo-PG - EC 3.2.1.67) from the thermophilic fungus Rhizomucor pu-sillus. The enzyme was produced by submerged cultivation and purified by chromatog-raphy and salting out. This has proved to be the most appropriate using 95 % ammoni-um sulfate, and with this technique it was possible to obtain the enzyme almost free of contaminants and with a yield of approximately 74 %. A subsequent step of hydropho-bic interaction chromatography is able to remove the remaining contaminants. The pure enzyme has molecular mass around 43.5-47 kDa, optimum pH of 4.0, optimum tem-perature of 61 °C, is stable at a pH range between 3.5 and 6.5, presents thermal stability from 30 to 60 °C and is activated in the presence Ca2+. The isoelectric point of the exo-PG is 6.2 and thermodynamic studies have shown that it is a thermophilic enzyme, highlighting its half-life t1/2 of 2,310 minutes at 50 °C. The profile of hydrolysis was ana-lyzed by capillary electrophoresis and studies indicate that the enzyme in this study has a pattern of sequential hydrolysis (exo). The identification of amino acids by mass spec-trometry MALDI-TOF and a comparison with data banks showed the highest identity of the sequenced fragments of exo-PG from R. pusillus with the corresponding enzyme from Aspergillus fumigatus. The application tests of the enzymes of the crude extract showed increased extra juice extraction and a higher yield in the hydrolysis process, but this was not observed with the pure enzyme